Optimalisasi Teknologi Informasi, Budaya Organisasi dan Kompetensi dalam Meningkatkan Kinerja Dosen (Tinjauan Pustaka) - Adi Muhajirin; Abdur Rahman Irsyadi; Fahmi Rizal; Sumaryono (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
This research is a literature review that aims to examine the relationship between information technology optimization, organizational culture, and competence with improving lecturer performance. In today's digital era, information technology plays an increasingly important role in higher education. Information technology optimization includes the utilization of technology to improve efficiency, productivity, and quality in academic and administrative activities. Organizational culture reflects the values, norms and practices prevailing within educational institutions. Lecturer competencies refer to the skills, knowledge and attitudes relevant to teaching and research tasks. Through the literature review, the relationship between information technology optimization, organizational culture, and competencies with lecturer performance improvement will be identified. The results of the literature review show that information technology optimization can improve the efficiency and productivity of lecturers in carrying out teaching, research, and administrative tasks. An organizational culture that supports innovation, collaboration, and technology utilization also contributes to improving lecturer performance. The technological knowledge and skills mastered by lecturers contribute significantly to their performance. Improving lecturers' competencies in technology use, understanding of digital curriculum, and technology-based teaching skills can also improve teaching and research effectiveness.